Argentina - Annunziata, Rocío (2016)
In this book we continue Plataforma Democrática's efforts to contributetowards the debate on the paths of democracy in Latin America and worldwide,focusing on the use made of the new means of communication by politicalactivists and how these in turn influence the ways in which politics is conducted.Contemporary democracies face enormous challenges: weakenedpolitical parties, global processes that redefine the national State spossibilities for action, social inequality and distrust of politicians. All theseareas and others not mentioned , are colored and influenced by thenew communication media.This book contains 19 case studies taken from six South Americancountries, presenting a broad range of innovative experiences and theirimpacts on the ways in which civil society, political parties and governmentsare organized and act. The cases of cyberactivism analyzed indicate that noneof them represents a silver bullet an experience capable of resolvingthe multiple challenges faced in constructing higher quality, more robustdemocratic institutions. But they all indicate new possibilities and newchallenges for the development of virtuous relations between the traditionalforms of participation (both in civil society organizations and in politicalparties) and activism in the virtual space.We are at the beginning of a new era, and there is much to learn,to monitor and to analyze. Without ignoring the fact that every attempt atsynthesis is partial and temporary, we hope that this book may contribute to the debate on a subject crucial for the future of democracy. Lastly, we wouldlike to acknowledge the important contribution made by the participants inthe workshops in which the preliminary versions of the texts on the diversecountries studied were presented.